Nature Tech Enterprise : Germinate Growing Booster / Ahmad Izzuddin Ahmad Zailani ...[et al.] - Ahmad Zailani, Ahmad Izzuddin; Kamal, Muhammad Hilmi Akmal; Mohktar, Muhammad Amiruddin; Mohamad Arifin, Muhammad Haziq (2017)
We serve and provide a machine that can increase the growth of plant that can provide enough nutrition to the plant. Other than that, our company also will sell this machine to the farmer to help them in agriculture. Hence, Nature Tech Enterprise will slowly gain market in the agricultural field. Apart from that, we are believe that we will successfully compete with our competitors in a few years ahead. This is because our company supplies products that can help farmers to develop their agriculture.